Kesehatan Mental dan Kebahagiaan: Tinjauan Psikologi Islam - Zulkarnain Zulkarnain; Siti Fatimah (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
Mental health is often associated with happiness, is a scientific study and promotion of psychological well-being and function optimization in individuals. Of course a normal person will display good and acceptable behavior in general. His attitude in accordance with the norms and patterns of community groups, so that there are satisfying interpersonal and intersocial relations. Healthy mental health condition is that they avoid the symptoms of mental disorders, symptoms of mental illness, show their intelligence, and have a happy life attitude. Mental health can be reviewed in two ways, negatively with the absence of mental disorders and positively when the presence of a healthy individual mental personality refers to positive conditions or traits. Happiness in humans, includes positive feelings (comfortable-enjoyable) and positive activities. The goals to be achieved are developing studies on mentally impaired individuals, suffering from mental disorders and mental illness into positive personalities and interventions that believe that every individual in various conditions has the potential, ability to understand their strengths and weaknesses, and the ability to function optimally for happiness.